2021
DOI: 10.1097/mpg.0000000000003230
|View full text |Cite
|
Sign up to set email alerts
|

Experience Using Ustekinumab in Pediatric Patients With Medically Refractory Crohn Disease

Abstract: Introduction:Ustekinumab (UST), a human monoclonal antibody against interleukin-12 and 23, is approved to treat adult patients with psoriasis or Crohn disease (CD). Outcomes data for off-label use in pediatric patients with CD are limited.Aim:We conducted a retrospective cohort study to analyze the long-term efficacy of UST, including dose adjustments, in the treatment of pediatric patients with medically refractory CD. Adverse events were documented.Methods:We identified 40 pediatric patients with CD treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…Moreover, the wPCDAI, the CRP, and FC levels decreased significantly. These results are in line with those of Kim et al (14) who studied the largest real-life pediatric cohort published to date. They reported a decline of abbreviated PCDAI from 25 to 5 and an increase in the clinical remission rate from 11% to 61%.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the wPCDAI, the CRP, and FC levels decreased significantly. These results are in line with those of Kim et al (14) who studied the largest real-life pediatric cohort published to date. They reported a decline of abbreviated PCDAI from 25 to 5 and an increase in the clinical remission rate from 11% to 61%.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 63 studies (including 8529 patients) met the inclusion criteria and were finally included in the systematic review and meta-analysis ( Figure 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Only one study focused exclusively on naïve patients [ 55 ], and in three studies, prior biologic exposure was not reported. Only three studies (4.8%) included paediatric patients [ 54 , 59 , 63 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some case reports suggest that 50% of children with IBD have a clinical response to ustekinumab ( 94 , 95 ). In a cohort of pediatric patients with CD, patients using ustekinumab had significant improvements in their abbreviated pediatric CD activity index (aPCDAI) scores, clinical remission rates, albumin, and hematocrit, and 89.5% of patients had no significant adverse events ( 96 ). The use of off-label drugs is increasing in children with IBD and generally they are being reported as safe and effective ( 93 ).…”
Section: Therapeutic Methodsmentioning
confidence: 99%